Дослідження Mo(VI) оксо-структур на поверхні цілеспрямовано створених модельних систем MoO3/Al2O3 ТА MoO3/SiO2 - Плюто, Ю.В.; Шаранда, Л.Ф.; Насєдкін, Д.Б.; Бабич, І.В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2024)
Model well-defined MoO3/Al2O3 and MoO3/SiO2 systems were rationally designed by anchoring of MoOCl4 on the supports surface of fumed Al2O3 and SiO2 nanoparticles. The subsequent hydrolysis of the anchored groups by water vapours followed by thermal treatment resulted in the formation of Mo(VI) oxo-species on the supports surface. By application of the anchoring – hydrolysis cycles the model MoO3/Al2O3 systems with the molybdena loading of 1.10, 1.92 and 2.34 Mo/nm2 were synthesised. The synthesised MoO3/SiO2 systems had a molybdena loading of 0.82, 1.05 and 1.21 Mo/nm2. X-ray diffraction patterns characteristic for MoO3 crystallites were not observed in the synthesised MoO3/Al2O3 and MoO3/SiO2 systems up to the highest achieved molybdena loading of 2.34 and 1.21 Mo/nm2 respectively. This confirms that the used preparation route resulted in the formation of highly dispersed Mo(VI) oxo-species on the surface of both Al2O3 and SiO2 supports. The degree of aggregation of Mo(VI) oxo-species depends on the nature of the support surface and molybdena loading. Increase of the molybdena loading on the surface of both Al2O3 and SiO2 supports results in an increase of the degree of aggregation of Mo(VI) oxo-species. On Al2O3 support, at a molybdena loading which corresponds to the population of surface hydroxyl groups, monomeric Mo(VI) oxo-species appear to be predominant. At higher molybdena loading, the formation of polymeric Mo(VI) oxo-species was detected. On SiO2 support, at a molybdena loading which corresponds or exceeds the population of surface hydroxyl groups, simultaneous presence of monomeric and polymeric Mo(VI) oxo-species was observed.